Penerapan Teknologi Computer Generated Imagery Pada Visual Effect Film - Dewi Immaniar; Lusyani Sunarya; Muhammad Alfian (CICES (Cyberpreneurship Innovative and Creative Exact and Social Science), 2015)
In modern times such as this, the world of entertainment, especially in the film really enjoy doing.Various types of films emerging and very interesting to watch. In the modern era oftelecommunications today, technology is very influential. Mainly in the manufacture of variousfilms. Start of animas to fiction films. At that moment the application of multimedia technology ofcomputer generated imagery is needed, to make a movie that the film will be alive and visible. Inthe filming of Transformers lot of computer generated imagery using this technology, because ofthe effects of a car that turns into a robot is not possible using the manual method such as dressingsets per set of movie. Therefore Computer Generated Imagery is used this technology. In theatmosphere of the original, just needed the room with the green screen background and then willbe processed into a computer and software specifications are quite high. Starting from the effectsof flying to the moon, meteor fall, the transformation changes the shape and use CGI effects,because otherwise the result would not be perfect. Thus the CGI technology is not only used in theTransformers movie pebuatan alone, but also on the making of the film to make it look morestunning and cool.